2011
DOI: 10.1021/jm101299d
|View full text |Cite
|
Sign up to set email alerts
|

Homodimeric Bis-Quaternary Heterocyclic Ammonium Salts as Potent Acetyl- and Butyrylcholinesterase Inhibitors: A Systematic Investigation of the Influence of Linker and Cationic Heads over Affinity and Selectivity

Abstract: A molecular library of quaternary ammonium salts (QASs), mainly composed of symmetrical bis-quaternary heterocyclic bromides exhibiting choline kinase (ChoK) inhibitory activity, were evaluated for their ability to inhibit acetyl- and butyrylcholinesterase (AChE and BChE, respectively). The molecular framework of QASs consisted of two positively charged heteroaromatic (pyridinium or quinolinium) or sterically hindered aliphatic (quinuclidinium) nitrogen rings kept at an appropriate distance by lipophilic rigid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…The synthesis of MN58b has been reported in two papers where it was referred to as Compound 41 (43, 44). In this paper, we include a detailed description of the synthesis of the intermediate 1,4-bis(4-bromomethylphenyl)butane (Figure 3B), which was not provided in the original papers (45, 46) or in either of the papers describing the synthesis of MN58b (43, 44). In addition, we have improved upon the synthesis of MN58b (Figure 3B) by employing an autoclave method following the phase transfer catalyzed bromomethylation (47).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synthesis of MN58b has been reported in two papers where it was referred to as Compound 41 (43, 44). In this paper, we include a detailed description of the synthesis of the intermediate 1,4-bis(4-bromomethylphenyl)butane (Figure 3B), which was not provided in the original papers (45, 46) or in either of the papers describing the synthesis of MN58b (43, 44). In addition, we have improved upon the synthesis of MN58b (Figure 3B) by employing an autoclave method following the phase transfer catalyzed bromomethylation (47).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we have improved upon the synthesis of MN58b (Figure 3B) by employing an autoclave method following the phase transfer catalyzed bromomethylation (47). This decreases the reaction time from 192 h (44) to 3 hours with 50% yield. The melting point of our MN58b product differs from that in (44), where it is reported as 161-163°C, but is consistent the values of 98-100°Cwhen the compound was crystallized from water (43).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10] In addition, quaternary nitrogen cation displays highly positive binding stabilization due to cation-π interactions with amino acid residues in AChE enzyme. [9][10][11][12] Many reports indicated that compounds bearing aromatic/ heteroaromatic rings on lateral parts of pyridinium displayed high AChE inhibitory activity and act as dual binding inhibitors.…”
mentioning
confidence: 99%
“…[5][6][7][8][9][10] In addition, quaternary nitrogen cation displays highly positive binding stabilization due to cation-π interactions with amino acid residues in AChE enzyme. [9][10][11][12] Many reports indicated that compounds bearing aromatic/ heteroaromatic rings on lateral parts of pyridinium displayed high AChE inhibitory activity and act as dual binding inhibitors. [13][14][15][16] According to the docking studies of these compounds, it was found that both terminal rings attached to the pyridinium were able to bind simultaneously to both CAS and PAS of the enzyme resulting in higher AChE inhibitory activity.…”
mentioning
confidence: 99%